Consumers’ Preference and Willingness to Pay for Nepalese Large Cardamom in the Global Market - Kattel, Rishi Ram; Regmi, Punya Prasad; Sharma, Moha Dutta; Thapa, Yam Bahadur (International Journal of Social Sciences and Management, 2020)
This paper examines the consumers’ preference and willingness to pay Nepalese large cardamom in the global market. A total of 255 respondents were surveyed using structural questionnaire in KoBo Toolbox online survey during 2019-2020. The Logit model was used for assessing factors determine consumers WTP and WTP regression was used to assess the monetary value of additional WTP price premium. Average age of the respondents were 29.21 years and 16.70 years of schooling. The average household size was 4.87 members. Two-third of respondents were male and 39% respondent’s occupations were service. About 92% respondents belonged to Asia whereas 38% from urban city origin. One-fourth of respondents had US$ 5000 and above annual income. Consumers were willing to pay price premium of 34.56% for Nepalese large cardamom while about 33% additional WTP for organically certified once. About 40% respondents willingness to pay of Nepalese large cardamom whereas 65% expressed their additional WTP on organic certified. Average price paid for cardamom was US$ 19.6 per kg whereas the WTP additional amount for Nepalese cardamom was US$ 6.92 per kg and US$ 6.6 per kg additional for organic certified once. Major determine factors on WTP of Nepalese cardamom were preference based on color, size, household expenditure and knowledge. Additional WTP of Nepalese large cardamom price premium were determined by preference based on color, size and part of cardamom used. The results can significantly contribute to improving value added practices of Nepalese cardamom based on consumers’ preference.